Effects of induced placental and fetal growth restriction, size at birth and early neonatal growth on behavioural and brain structural lateralization in sheep. Issue 5 (3rd September 2017) - Hunter, Damien Seth; Hazel, Susan J.; Kind, Karen L.; Liu, Hong; Marini, Danila; Giles, Lynne C.; De Blasio, Miles J.; Owens, Julie A.; Pitcher, Julia B.; Gatford, Kathryn L.
ABSTRACT: Poor perinatal growth in humans results in asymmetrical grey matter loss in fetuses and infants and increased functional and behavioural asymmetry, but specific contributions of pre- and postnatal growth are unclear. We therefore compared strength and direction of lateralization in obstacle avoidance and maze exit preference tasks in offspring of placentally restricted (PR: 10M, 13F) and control (CON: 23M, 17F) sheep pregnancies at 18 and 40 weeks of age, and examined gross brain structure of the prefrontal cortex at 52 weeks of age (PR: 14M, 18F; CON: 23M, 25F). PR did not affect lateralization direction, but 40-week-old PR females had greater lateralization strength than CON ( P = .021). Behavioural lateralization measures were not correlated with perinatal growth. PR did not alter brain morphology. In males, cross-sectional areas of the prefrontal cortex and left hemisphere correlated positively with skull width at birth, and white matter area correlated positively with neonatal growth rate of the skull (all P < .05). These studies reinforce the need to include progeny of both sexes in future studies of neurodevelopmental programming, and suggest that restricting in utero growth has relatively mild effects on gross brain structural or behavioural lateralization in sheep.